From Palaces-Delubrums to Palaces-Simulacrums - Elena Bagina (Proekt Bajkal, 2016)
Today the notion of palace is rather vague. It unites artistically and functionally heterogeneous buildings. Historically, there are two types of palaces: a palace-delubrum (Ancient times, Middle Ages) and a palace-artwork (epochs of absolute monarchies). From the middle of the 19th century different public buildings that had no relation to power representation were called palaces: the Chrystal Palace, the Palace of Nations, etc. In the USSR there were Palaces of Culture, Palaces of Soviets, Palaces of Labour, etc. Such public buildings can be called palaces-simulacrums, which are to cultivate democratic illusions in the society. The museeficated old-time palaces are a dead ‘outer body’ of the deceased rulers. Palaces remain alive only when they are abodes of the Power.